Developing Formative Assessment on Procedure Text through Socrative for Tenth Grade Students at MAN 2 Model Medan - Yumna Azzahra; Safrida Lubis (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2025)
This research aimed to develop a formative assessment on procedure text through Socrative for tenth grade students at MAN 2 Model Medan. This research was conducted because it was found that the student still use the traditional formative assessment. The research followed the Research and Development (R&D) method, consisting of six stages: gathering information and data, analyzing the data, designing the media, validating by experts, revising, and producing the final product. The subjects of the study included 36 students from class X-N and one of the English teacher. The data were collected by interviewing the English teacher and administering a questionnaire to the students to assess their needs. The results indicated that the students need a developing of formative assessment through Socrative. The product was validated by two experts: an English lecturer and an English teacher. The validation process included evaluating linguistic aspects, the assessment process, the product and content, and the layout of the media. The product received an overall validation score of 93.95%, indicating that the formative assessment developed through Socrative is suitable for use in the classroom. Based on this validation, the formative assessment is considered effective and appropriate for improving the learning experience of tenth grade students at MAN 2 Model Medan, particularly in enhancing their understanding of reading procedure texts.